PELAKSANAAN PERATURAN DAERAH PROVINSI BALI NOMOR 9 TAHUN 2009 TERKAIT DENGAN POGRAM WAJIB BELAJAR 12 TAHUN - Ni Nyoman Budi Sentana (University of Udayana, 2014)
The local government of Bali Province issued a policy that was formulated in The Local Regulation of Bali Province Number 9 of 2009. In appendix of The Local Regulation Number 9 of 2009 is described a 12-year compulsory education. This study discusses the effectiveness of The Local Regulation of Bali Province Number 9 of 2009 related to the implementation of 12-years compulsory education in Bali Province and the factors that influence the effectiveness of the implementation of The Local Regulation Number 9 of 2009 related to the implementation of 12-years compulsory education in Bali Province. This research is empirical legal research. The nature of research is descriptive. The data in this study include primary data that was collected through interview techniques and secondary data that was collected through the study of literature. The research location is in Bali Province with sample in Denpasar and Bangli regency. The data collected was analyzed qualitatively and descriptively presented analytically. Effectiveness of The Local Regulation of Bali Province Number 9 of 2009 related to the implementation of 12-years compulsory education in Bali Province is not optimal in some areas. The factors that influence the effectiveness of the implementation of The Local Regulation Number 9 of 2009 related to the implementation of 12-years compulsory education in Bali Province are legal factors, law enforcement factor, means and facilities in law enforcement factor, community factors and cultural factors